A new species of Oberonia (Orchidaceae) from Western Ghats of Kerala, India. (31st May 2018) - Prasad, Kothareddy; Sudheshna, Pemmu; Prabhukumar, K. M.
Abstract : A new Oberonia species, O. muthikulamensis (Orchidaceae), is described and illustrated from Muthikulam forest, Western Ghats of Kerala, India. It is compared with a closely morphologically similar species, O. sebastiana, endemic to Western Ghats.